Respuesta :

Answer:

The value of y = 0.6 when x = -1.

Step-by-step explanation:

Given

  • y = -3
  • x = 5

To determine

Find 'y' when x = -1

  • Two quantities can be termed as vary with each other directly if a change in one quantity established a proportional change in the other quantity.

As y directly with x, we express it as:

y ∝ x

y = kx

here 'k' is called the constant of variation

substituting y = -3 and x = 5 to determine the 'k'

y = kx

k = y/x = -3/5

As we have to find 'y' when x = -1

y  = kx

so substituting x = -1 and k = -3/5

y = (-3/5) (-1)

y  = 3/5

y = 0.6

Therefore, the value of y = 0.6 when x = -1.

ACCESS MORE